Struś - nowe źródło mięsa drobiowego. Użytkowanie mięsne i jakość mięsa - Haraf, Gabriela (Ostrich - the New Source of Poultry Meat. Slaughter Performance and Quality of Ostrich Meat, 2008)
The paper presents the characteristic of slaughter value of ostrich, sensory traits and chemical composition of ostrich meat as well as comparison with other kinds of meats. Ostrich meat has high nutritional value and unique taste. From a nutritional point of view, it is worthy of interest because of advantageous fatty acids profile, high protein and iron content, as well as low cholesterol and sodium content. Ostrich meat does not have any negative sensory traits compared to other animal species. The meat is quite popular with consumers in USA and West European countries, but there is minimal demand for the ostrich products in Poland because of their high price. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 11-23